The effect of aerobic exercise training on work ability of midwives working in health care centers - Zahra Abedian; Minoo Safaei; Seyed Reza Mazlum; Seyed Reza Attarzadeh Hoseini (Mashhad University of Medical Sciences, 2017)
Background & aim: Maintaining and improving the work ability are important social goals, which challenge the health care and rehabilitation systems as well as health providers. The physical and mental health status affect the work ability. Regarding this, the current study aimed to investigate the effect of aerobic training on the work ability of the midwives in the health care centers of Mashhad, Iran in 2013. Methods: This randomized clinical trial was conducted on 60 midwives working in the health centers of Mashhad, Iran, using purposeful sampling method. The health care centers were selected randomly, and then assigned into the intervention and control groups. Subsequently, the intervention group performed aerobic exercise for 24 sessions. Data collection was performed using the work ability index and the Bruce test (to compare the fitness of the participants at the pre- and post-intervention stages). For data analysis, the two-way ANOVA, Mann-Whitney U, and Chi-square tests as well as independent and paired sample t-tests were employed, using SPSS version 19. The P-value less than 0.05 was considered statistically significant. Results: According to the results of the study, the mean score of work ability was significantly higher in the intervention group than that in the control group (40.5±4.9 vs. 36.4± 5.3, respectively; P=0.004). Furthermore, there was a significant difference between the two groups regarding the two variables including work ability compared with life time best (P